Localization of mandibular foramen relative to landmarks in East Indian mandibles - Kumari Sandhya; Bhoopendra Singh; Namita Lugun; Renu Prasad (Wolters Kluwer Medknow Publications, 2015)
Context: The position of mandibular foramen (MF) is an important anatomical landmark for effective anesthesia in dentistry for many procedures, including dental extraction from the lower jaw and putting mandibular implants. Several causes have been examined in this context, and the uncertainty in the location of the MF has been examined to be a major factor for the high failure rate of anesthesia and complications of the orthodontic procedure. Aims: The purpose of this study was to examine and analyze the position of the MF relative to six bony landmarks on the ramus in the population of Jharkhand. Subjects and Methods: The different parameters were measured in 30 dry adult's mandibles that were obtained from the Department of Anatomy. The data were tabulated and statistically analyzed. Statistical Analysis Used: Paired t-test. Results: The mean distance between the MF and the respective landmarks was noted as 16.00 ± 3.50 mm for the anterior border, 10.21 ± 2.34 mm for the posterior border, 20.48 ± 3.89 mm for the superior border, 24.15 ± 4.97 mm for the inferior border, 33.46 ± 6.08 mm for the condyle, and 12.31 ± 4.88 mm for the internal oblique ridge for the right side. On the left side, these distances were 16.27 ± 3.9 for the anterior border, 10.28 ± 5.24 for the posterior border, 20.15 ± 3.8 for superior border, 24.86 ± 4.04 for inferior border 32.48 ± 4.73 for condyle, and 10.93 ± 4.06 for the inferior oblique ridge. Statistically, there was no significant difference in the distance to either side from selected 5 landmarks, the only exception being the condyle. Conclusions: Condyle and internal oblique ridge have been shown to be two new landmarks that may be used to find MF. Bilateral symmetry has been shown for all landmarks except for condyle.